Validity of RIPASA scoring system as a diagnostic tool of acute appendicitis in comparison with Alvarado scoring system in the Arab population - Abdelrhman, Tamer M.; Al Saeed, Mohammed S.; Badr, Samir A.; Shaban, Mohamed A.; Abuduruk, Aseel; Hatem, Mohamed (International Surgery Journal, 2018)
Background: RIPASA scoring has been developed to replace the disappointingly low accuracy Alvarado score in Asian population for diagnosis of acute appendicitis. Objective of present study was to compare the RIPASA and Alvarado score in Arab population and determine their accuracy when applied to our patients in Egypt and Kingdom of Saudi Arabia (KSA). Methods: By applying the RIPASA and Alvarado scores to 100 patients from KSA, 100 patients from Egypt who presented to emergency with right iliac fossa pain. The decisions for appendicectomy were based on clinical judgment only. Histopathology as gold standard was correlated with both scores. ROC curve analysis, sensitivity, specificity, positive predictive value and negative predictive value, diagnostic accuracy for RIPASA and Alvarado system were calculated using SPSS version 20. Results: On comparing both the scoring system in patients of both hospital groups, we found that sensitivity of RIPASA scoring is greater than Alvarado scoring system 95.51% and 73.03% respectively in BTH group, and 97.56% and 79.27% respectively in KASH group, while the specificity of RIPASA scoring system is less than Alvarado scoring system 72.73% and 81.82% respectively in BTH group and 66.67% and 83.33% respectively in KASH group. Conclusions: In our Arab population the RIPASA score could be applied in diagnosis of acute appendicitis with higher sensitivity, NPV and diagnostic accuracy compared to the Alvarado score.